The Diagnostic Role of Abductor Pollicis Brevis - First Dorsal Interosseous (APB-FDI) Index in Diagnosing Amyotrophic Lateral Sclerosis (ALS) (Journal of Dhaka Medical College, 2025)
Background: This study aimed to assess the diagnostic role of the Abductor Pollicis Brevis - First Dorsal Interosseous (APB-FDI) Index in the diagnosis of Amyotrophic Lateral Sclerosis (ALS) among the Bangladeshi population. It also compared its diagnostic performances with first dorsal interosseous first dorsal interosseous and abductor digiti minimi (FDI-ADM) and (ADM-APB) ratios measuring the split hand phenomenon.Methods: This cross-sectional study was carried out in the Department of Neurology, Sir Salimullah Medical College & Mitford Hospital, and Dhaka Medical College Hospital, Dhaka, from March 2019 to September 2021. It also determined the APB-FDI index in ALS patients and compared the findings with age and gender-matched healthy control and disease control (Hirayama disease). The data was analyzed with receiver operating characteristic (ROC) curves and calculated area under the curve (AUC) for each ratio. Integrated discrimination improvement (IDI) and Decision Curve Analysis (DCA) to compare diagnostic accuracy over FDI-ADM and ADM-APB ratios.Results: Total 43 people were studied with ALS, 30 healthy people, and 10 Hirayama patients. The cutoff values of APB-FDI Index, ADM-APB ratio, and FDI-ADM ratio are 4.27, 1.04, and 2.20 respectively. The APB-FDI Index has a high AUC of 0.9, with good sensitivity and specificity. However, for Hirayama disease, the APB-FDI Index cutoff value is 11.6. The APB-FDI Index is clinically effective with optimal threshold probabilities identified through the Youden-Index ((APB- FDI Index-0.72, ADM-APB CMAP amplitude ratio-0.51, and FDI-ADM CMAP amplitude ratio- 0.17). Its standardized net benefits exceed healthy control and Hirayama when risk thresholds are between 0.1 and 0.8. The IDI results showed that the APB-FDI Index was superior to the ADM-APB ratio and FDI-ADM ratio.Conclusion: APB-FDI Index is the sensitive, specific, and early diagnostic marker for ALS.J Dhaka Med Coll. 2024; 33(1) : 7-17